Lymphatics and bone. - Edwards, J; Williams, K; Kindblom, L; Meis-Kindblom, J; Hogendoorn, P; Hughes, D; Forsyth, R; Jackson, D; Athanasou, N (2008)
There is controversy regarding whether lymphatic vessels are present or absent in bone. Although lymphangiomas have been described in bone, lymphatic vessels have not been identified morphologically with certainty in any other benign or malignant bone tumors or in normal human bone. In this study, we determined by immunohistochemistry, using 2 specific lymphatic endothelial cell markers, LYVE-1 and podoplanin, whether lymphatics are present in normal bone and a wide range of primary and secondary bone neoplasms. In normal bone, LYVE-1+/podoplanin+ lymphatic vessels were not identified in cortical or cancellous bone but were seen in connective tissue overlying the periosteum. With the exception of lymphangioma, Gorham-Stout disease, and hemangioendothelioma, primary benign and malignant bone tumors (as well as secondary carcinomas) that were confined to bone did not contain lymphatic vessels. Primary and secondary bone tumors that had extended through the bone cortex contained LYVE-1+/podoplanin+ lymphatic vessels that seemed to extend for a short distance from surrounding soft tissues into the tumor. Three cases of osteosarcoma that had extended through the bone cortex and had lymph node metastases were all found to contain lymphatic vessels within the tumor. These results indicate that the lymphatic circulation is unlikely to play a role in bone fluid transport in normal bone and that lymphatic vessels are absent from most primary and secondary tumors confined to bone. These findings also suggest that lymphangiogenesis is not involved in the disease progression of most primary bone tumors and that carcinomatous metastasis to bone does not occur via lymphatics.